Profil Sensori Minuman Jeli Ekstrak Air Daun Salam Kombinasi Jus Jambu Menggunakan Quantitative Descriptive Analysis: Sensory Profiling of Jelly Drink Made from a Combination of Bay Leaf Water Extract and Guava Juice Using a Quantitative Descriptive Analysis - Putri, Sefanadia; Marliyati, Sri Anna; Setiawan, Budi; Rimbawan, Rimbawan; Yunianto, Andi Eka; Rusyana, Asep (Universitas Airlangga, 2024)
Background: The profiling of a drink made from bay leaves combined guava juice has not been previously reported despite the positive health aspects of both plants. Objectives: To analyze the sensory characteristics of jelly drink bay leaf water extract with guava juice combination using the Quantitative Analysis Descriptive (QDA) sensory evaluation method. Methods: The QDA carried out of three stages, namely the panelist preparation stage, Forum Group Discussion (FGD), and quantitative descriptive test. QDA was carried out on four jelly drink product formulas, namely F0 (standard), F1 (75:25), F2 (50:50), F3 (25:75) from the ratio of bay leaf extract:guava juice. Results: Sensory attributes consist of 17 attributes, namely appearance (particle aggregation size, viscosity, homogeneity), aroma (bay leaf, guava, sweet), texture (gritty, ease of spreading), taste (guava, sweet, sour, bay leaf), mouthfeel (gritty, jelly-like consistency, viscosity), aftertaste (astringent and bitter). The results of the one-way ANOVA analysis showed significant differences between the formula and the control product (p<0.05). Formula 1 and 3 not accepted by consumers because there are weaknesses, such as the inhomogeneous appearance and the strong aroma of bay leaf obtained the highest value in formula 1. In contrast, formula 3 has the highest value in astringent and bitter aftertaste, gritty texture and mouthfeel. Conclusions: The selected treatment is formula two of jelly drink with a ratio of bay leaf water extract: guava juice = 50:50. A description like this will assist food technology in developing new products.